Comammox—a newly discovered nitrification process in the terrestrial nitrogen cycle - Hu, Hang-Wei; He, Ji-Zheng (Journal of soils and sediments, 2017)
Purpose Nitrification, the microbial oxidation of ammonia to nitrate via nitrite, is a pivotal component of the biogeochemical nitrogen cycle. Nitrification was conventionally assumed as a two-step process in which ammonia oxidation was thought to be catalyzed by ammonia-oxidizing archaea (AOA) and bacteria (AOB), as well as nitrite oxidation by nitrite-oxidizing bacteria (NOB). This long-held assumption of labour division between the two functional groups, however, was challenged by the recent unexpected discovery of complete ammonia oxidizers within the Nitrospira genus that are capable of converting ammonia to nitrate in a single organism (comammox). This breakthrough raised fundamental questions on the niche specialization and differentiation of comammox organisms with other canonical nitrifying prokaryotes in terrestrial ecosystems. Materials and methods This article provides an overview of the recent insights into the genomic analysis, physiological characterization and environmental investigation of the comammox organisms, which have dramatically changed our perspective on the aerobic nitrification process. By using quantitative PCR analysis, we also compared the abundances of comammox Nitrospira clade A and clade B, AOA, AOB and NOB in 300 forest soil samples from China spanning a wide range of soil pH. Results and discussion Comammox Nitrospira are environmentally widespread and numerically abundant in natural and engineered habitats. Physiological data, including ammonia oxidation kinetics and metabolic versatility, and comparative genomic analysis revealed that comammox organisms might functionally outcompete other canonical nitrifiers under highly oligotrophic conditions. These findings highlight the necessity in future studies to re-evaluate the niche differentiation between ammonia oxidizers and their relative contribution to nitrification in various terrestrial ecosystems by including comammox Nitrospira in such comparisons. Conclusions The discovery of comammox and their broad environmental distribution added a new dimension to our knowledge of the biochemistry and physiology of nitrification and has far-reaching implications for refined strategies to manipulate nitrification in terrestrial ecosystems and to maximize agricultural productivity and sustainability.